Carbon-efficient scheduling problem of electric rubber-tyred gantry cranes in a container terminal. Issue 12 (2nd December 2022) - Chen, Sumin; Zeng, Qingcheng
Abstract : Green container terminals have gained much attention to satisfy the demand for sustainable and environmentally friendly transport. As one of the major polluters in container terminals, rubber-tyred gantry cranes have already been widely replaced by electric rubber-tyred gantry cranes (ERTGs). This article exploits the features of ERTGs and studies the ERTG scheduling problem in container terminal yards considering the carbon dioxide emissions and task delays simultaneously. The problem is converted into a selective vehicle routing problem with soft time windows (SVRPSTW) and formulated as a mixed integer linear programming model. A column generation algorithm embedded in a branch-and-bound framework is employed to solve the problem. A hybrid acceleration strategy combining the label-setting algorithm with a tabu search algorithm is proposed. Finally, the proposed method is validated via computational experiments. The proposed method provides an efficient tool for carbon-efficient scheduling of ERTGs and thus contributes to the development of green ports.